Vaginal delivering after five caesarean sections - J. A. Coconina; M. Yu. Korshunov; U. M. Chuprun; S. D. Churakova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
This article presents a clinical case of the first vaginal delivery of the 44-year-old patient, who previously had five caesarean sections. the patient arrived at the hospital during the beginning of the second stage of labor. According to an mri-test conducted two months after the delivery, the thickness of myometry in the scars area of the uterus ranged from 7 to 16 mm.